Comparison of different methods to measure structural damping - Richter, Jan-Gerrit; Zeitler, Berndt; Sabourin, Ivan; Schoenwald, Stefan (Canadian Acoustics, 2011)
Structural damping indicates the energy loss in materials and systems respectively. Hereby, different loss mechanisms must be distinguished: namely internal losses or material damping due to conversion of kinetic energy into heat and coupling losses due to transmission of energy to adjoining systems. The reverberation time was obtained by exciting the specimen with a small force hammer at three positions using three repeats and measuring the acceleration at eight points distributed over the specimen. Schroeder Plots. A very simplistic approach is used assuming a circular bending wave front around a point source on an isotrupic infinite plate in the far field. The low agreement of the drawaway method is explained by the multiple simplifications made by the model. Even in the midrange frequency bands, reflections make detecting a clear decay impossible. At low frequencies the near field additionally distort the vibration pattern especially closer to the excitation point.